1996
DOI: 10.1021/jo960910s
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis. 39.1 Synthesis of 2-(1-Aminoalkyl)piperidines via 2-Cyano-6-phenyl Oxazolopiperidine

Abstract: The asymmetric synthesis of a series of 2-(1-aminoalkyl) piperidines using (-)-2-cyano-6-phenyloxazolopiperidine 1 is described. LiAlH(4) reduction of 1 followed by hydrogenolysis led to the diamine 3. The same strategy applied to C-2-methylated compound 7 afforded [(2S)-2-methylpiperidin-2-yl]methanamine (9). Addition of lithium derivatives to the cyano group of 1 resulted in the formation of an intermediate imino bicyclic system (11a-c) which could be diastereoselectively reduced to substituted diamino alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Halogen/metal exchange of 269a and 269b each with butyl lithium led to the formation of the lithiated intermediate, which was transformed into the imines 270a and 270b (91% and 84% yields) (Scheme ) . The epimino‐chromenoazepines 270 were obtained through the intramolecular addition of the aryl‐lithium onto the cyano group and subsequent attack of imine salt on the angular C8a atom of the prospective iminium ion …”
Section: Reactionssupporting
confidence: 71%
“…Halogen/metal exchange of 269a and 269b each with butyl lithium led to the formation of the lithiated intermediate, which was transformed into the imines 270a and 270b (91% and 84% yields) (Scheme ) . The epimino‐chromenoazepines 270 were obtained through the intramolecular addition of the aryl‐lithium onto the cyano group and subsequent attack of imine salt on the angular C8a atom of the prospective iminium ion …”
Section: Reactionssupporting
confidence: 71%
“…[16] The relative configuration of the newly created stereogenic center (C-7) of 5b was determined directly from the NMR spectroscopic data and by comparison with the literature. [17] Indeed, the 2-H/7-H coupling constant of 4.5 Hz indicates a R/R configuration for the C-2/C-7 stereocenters.…”
Section: Resultsmentioning
confidence: 98%
“…Further, these methods frequently result in competitive side reactions, notably in the presence of benzylamines and α-amino ethers, groups that are readily hydrogenolysable and reducible, respectively. Previous studies have shown, for example, that α-amino ether moieties are not tolerated by DI-BALH, LiAlH 4 , [13] or NaBH 4 . [14] Given the structural features of our compounds, it is necessary to find reaction conditions that are selective for the removal of the cyano group without opening of the oxazolidine ring and/or without cleavage of the chiral auxiliary.…”
Section: Reductive Decyanationmentioning
confidence: 98%
“…Moreover, close similarities in the NMR spectra of 4a and 7a as well as those of 4b and 7b allowed us to assign the stereochemistry at C-6 in 7a and 7b. For example, the 13 C chemical shifts of C-6 for 7b (δ ϭ 87.4 ppm) and C-2 for 4b (δ ϭ 89.1 ppm) are both nearly identical and upfield with respect to those of the corresponding carbon atoms in 7a (δ ϭ 94.3 ppm) and 4a (δ ϭ 95.7 ppm). These comparisons and correspondences can be accounted for by an axial position for 6-H in 7a and an equatorial one in 7b.…”
Section: Reductive Decyanationmentioning
confidence: 99%